Trends and Impact of Sustainable Energy Technologies in Mechanical Engineering: A Bibliometric Study - Gusti Rusmayadi; Supriandi, Supriandi; Pahrijal, Rival (Westscience Press, 2023)
The urgent environmental issues of the twenty-first century, particularly climate change, have thrust mechanical engineering into a central position in the creation of novel technologies for a future centered on sustainable energy. From energy-efficient mechanical designs to renewable energy systems, sustainable energy technologies provide a wide range of solutions. This bibliometric analysis uses sophisticated tools, such as VOSviewer, to examine a large dataset of academic articles in mechanical engineering that deal with sustainable energy technology. Dominant research themes, significant writers, collaborative networks, and prominent journals are identified by the study. Important discoveries include the notable increase in research output during the previous 20 years, the rise to prominence of notable writers and research teams, the connection between research themes, and the critical importance of particular papers and journals. These revelations help to shape a more sustainable and ecologically conscious energy future by offering a road map for navigating the complex world of sustainable energy in mechanical engineering.